The effect of energy poverty reduction and renewable energy use on CO2 emissions: empirical evidence from ASEAN countries - Gür, Betül; Sart, Gamze; Karamıklı Çetin, Aysun; Bayar, Yılmaz (Frontiers in Environmental Science, 2025)
Access to affordable and clean energy and increasing CO2 emissions are among the leading global challenges. Energy is one of the fundamental requirements of life, and, in turn, problems regarding access to energy include many negative educational, health, environmental, and economic implications for nations. On the other hand, increasing CO2 emissions can negatively impact societies through global warming, climate change, and air pollution. For this reason, this research investigates the influence of energy poverty, the use of renewable energy, and per capita GDP on CO2 emissions in the ASEAN states for the years 2000–2021 through causality and co-integration methods. The outcomes of the causality test uncover a significant effect of per capita GDP and energy poverty indicators on CO2 emissions and a bidirectional causal relation between CO2 emissions and the use of renewable energy. In addition, the outcomes of the co-integration analysis unveil that the effect of energy poverty indicators on CO2 emissions differs among the ASEAN countries. In conclusion, advancement in access to energy through clean energy sources and energy-efficient technologies is beneficial for improvements in the environmental quality.